Boeravinone B in Herbal Medicine: A Review on Analytical Methods, HPLC Validation, and Phytochemical Standardization - Agrawal, Om Prakash; Chauhan, Aparna; Gulati, Puja (Journal of Neonatal Surgery, 2025)
Boeravinone B, a key rotenoid found in Boerhaavia diffusa and Mirabilis jalapa, exhibits significant pharmacological activities, including antioxidant, anti-inflammatory, and hepatoprotective effects. Accurate quantification and standardization of Boeravinone B are essential for ensuring the efficacy and quality of herbal formulations. This review discusses various analytical techniques, with a focus on High-Performance Liquid Chromatography (HPLC), for the detection, quantification, and validation of Boeravinone B in herbal extracts. Additionally, it explores phytochemical standardization approaches to maintain batch-to-batch consistency in herbal medicine